2013
DOI: 10.3233/jad-130842
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Progression to Dementia in Elderly Subjects with Mild Cognitive Impairment Using Both Cognitive and Neuroimaging Predictors

Abstract: The objective of this work was to assess the predictive accuracy of targeted neuroimaging and neuropsychological measures for the detection of incipient dementia in individuals with mild cognitive impairment (MCI), and to examine the potential benefit of combining both classes of measures. Baseline MRI measures included hippocampal volume, cortical thickness, and white matter hyperintensities. Neuropsychological assessment focused on different aspects of episodic memory (i.e., familiarity, free recall, and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 64 publications
7
43
0
1
Order By: Relevance
“…This is consistent with the observation that MCI is mainly characterized by memory deficits [3,5], and that both episodic memory and working memory are impaired early in the disease process and are predictors of conversion from MCI to AD [11,36] (for a review, see [37]) and from healthy aging to MCI [38].…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the observation that MCI is mainly characterized by memory deficits [3,5], and that both episodic memory and working memory are impaired early in the disease process and are predictors of conversion from MCI to AD [11,36] (for a review, see [37]) and from healthy aging to MCI [38].…”
Section: Discussionsupporting
confidence: 88%
“…In the same vein, in Schmand et al, 47 combining a verbal episodic memory score, hippocampal volume and cerebrospinal fluid amyloid measure correctly predicted progression from MCI to AD with an accuracy of 70%, whereas classification accuracy was below 70% for each individual measure. Similarly, Peters et al 86 indicated that cortical thickness of the anterior cingulate gyrus combined to specific memory measures yielded a classification accuracy of 87.5% in the discrimination between stable MCI versus MCI who developed AD. These were considered more accurate predictions than those based on neuroimaging (75%) or cognitive measures (82.5%) alone.…”
Section: Neuropsychological Assessments That Best Predict Admentioning
confidence: 93%
“…Another study observed an age-dependent progression in insulin signaling dysregulation that precedes peripheral insulin resistance in two preclinical AD models [87]. Hippocampal dysfunction and structural compromise are one of the early signs during AD onset [87-91]. Insulin plays a very important role in AD progression by various complex mechanisms [92].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%